2017
DOI: 10.1111/bjso.12214
|View full text |Cite
|
Sign up to set email alerts
|

‘Where there is a will, there is a way’: Belief in school meritocracy and the social‐class achievement gap

Abstract: Meritocratic ideology can promote system justification and the perpetuation of inequalities. The present research tests whether priming merit in the school context enhances the effect of socioeconomic status (SES) on school achievement. French fifth graders read a text priming either school merit or a neutral content, reported their French and mathematics self-efficacy as well as their belief in school meritocracy (BSM), and then took French and mathematics tests. Compared to the neutral condition, the merit p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 48 publications
1
35
0
6
Order By: Relevance
“…Fourteen experiments were conducted within an applied field. The majority were conducted in an organizational context (e.g., Castilla and Benard, 2010), two studies took place in the educational context (Darnon et al, 2017, 2018), two others were aggregated into a health-related domain (Quinn and Crocker, 1999; Newsom, 2014), two experiments were conducted within moral dilemmas scenarios (Moreira, 2016) and one in a social domain (Levy et al, 2006). The remainder experiments were unspecified domain-wise.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen experiments were conducted within an applied field. The majority were conducted in an organizational context (e.g., Castilla and Benard, 2010), two studies took place in the educational context (Darnon et al, 2017, 2018), two others were aggregated into a health-related domain (Quinn and Crocker, 1999; Newsom, 2014), two experiments were conducted within moral dilemmas scenarios (Moreira, 2016) and one in a social domain (Levy et al, 2006). The remainder experiments were unspecified domain-wise.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed overview of the Meritocracy Activation (MA) is depicted in Table S1. Five multi- experiments present an original prime aiming to activate aspects of the Meritocracy construct (Chatard et al, 2006; McCoy and Major, 2007; Pereira et al, 2009; Castilla and Benard, 2010; Redersdorff et al, 2016; Darnon et al, 2017, 2018), four primes focused on Protestant Work Ethic (Katz and Hass, 1988; Biernat et al, 1996; Quinn and Crocker, 1999; Levy et al, 2006) and two primes focused on perceptions of success and social mobility (Ho et al, 2002; Ryan et al, 2012). The remaining used either the same and modified version of the original or one of the primes mentioned above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the extent that this helps middle‐class children to outperform their working‐class peers, the ‘meritocratic’ belief that such performance differences are due to differences in ability and/or effort will serve to ‘explain’ and legitimate unequal performance. Consistent with this argument, Darnon, Wiederkehr, Dompnier, and Martinot () primed the concept of merit in French fifth‐grade schoolchildren and found that this led to lower scores on language and mathematics tests – but that this only applied to low‐SES children. Moreover, the effect of the merit prime on test performance was mediated by the extent to which the children endorsed meritocratic beliefs.…”
Section: Contexts That Shape Self‐construal: Home School and Workmentioning
confidence: 87%
“…First, education has become a key predictor of life chances (e.g., [12]), making social inequalities in educational outcomes especially important. Second, education is highly valued in societies and often perceived to be a countervailing force against classbased inequalities, yet evidence demonstrates that educational institutions channel and reinforce inequalities [3,13,14,15,16,17]. Third, differences in education are fueling contemporary political rifts.…”
Section: Introductionmentioning
confidence: 99%